2024: anticipating record-breaking performances in front crawl swimming through mathematical analysis - Patoz, A.; Finiel, L.; Borrani, F. (Frontiers in Physiology, 2024)
Introduction: This study presented a novel approach to predict future front crawl swimming world records (WRs) by employing a methodology that integrated performance data from both running and front crawl swimming.